PROSES BERPIKIR REFRAKTIF SISWA INTROVERT - Sari, Putri Diana; Putra, Eric Dwi; Sulisawati, Dwi Noviani (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2022)
The importance of critical thinking skills in problem solving is one of the objectives of implementing learning. While the ability to analyze and summarize the information obtained is called reflective thinking. This study aims to describe how students' reflective thinking processes during problem solving. Subjects needed in this study amounted to 1 student selected from 30 students of class IX D SMP Negeri 5 Jember. The data was collected by using the method of tests, questionnaires and interviews with analytical techniques including data reduction, presentation and drawing conclusions. The results showed that the refractive thinking process of introverted students started from gathering information and interpreting it. Furthermore, students connect the existing information with the knowledge they have. The subject had no other alternative in solving the problem, so there was no reason for him to had a strategy that had been implemented. However, introverted students were able to find the right answers and checked the answers they received.